2003
DOI: 10.3758/bf03196520
|View full text |Cite
|
Sign up to set email alerts
|

What a speaker’s choice of frame reveals: Reference points, frame selection, and framing effects

Abstract: Framing effects are well established: Listeners' preferences depend on how outcomes are described to them, or framed. Less well understood is what determines how speakers choose frames. Two experiments revealed that reference points systematically influenced speakers' choices between logically equivalent frames. For example, speakers tended to describe a 4-ounce cup filled to the 2-ounce line as half full if it was previously empty but described it as half empty if it was previously full. Similar results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
144
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(160 citation statements)
references
References 27 publications
11
144
1
4
Order By: Relevance
“…Different ways of describing the same problem should not lead to different inferences or conclusions, as long as the facts remain unchanged. More recently, McKenzie and colleagues (McKenzie & Nelson, 2003;Sher & McKenzie, in press) have suggested that different frames are not informationally equivalent, in fact they ''leak'' information about expectations and reference values. When we talk about lives lost, we are talking about negative outcomes, and are making an implicit comparison to a state of affairs where fewer lives are lost.…”
Section: Discussionmentioning
confidence: 99%
“…Different ways of describing the same problem should not lead to different inferences or conclusions, as long as the facts remain unchanged. More recently, McKenzie and colleagues (McKenzie & Nelson, 2003;Sher & McKenzie, in press) have suggested that different frames are not informationally equivalent, in fact they ''leak'' information about expectations and reference values. When we talk about lives lost, we are talking about negative outcomes, and are making an implicit comparison to a state of affairs where fewer lives are lost.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, people's reactions indicated that a general theory about the effects of framing on choice is probably not part of our folk-psychological makeup (Perner & Kühberger, 2002). That is, lay people won't have a relevant general theory on framing available, neither explicit nor implicit, neither precise nor vague (see McKenzie & Nelson, 2003). Successful prediction of the effect therefore is unlikely to be based on theory.…”
Section: Predicting Decisionsmentioning
confidence: 99%
“…If choice in framing tasks is based on extracted gist, and if gist extraction is not treated as a distortion, the framing effect cannot be considered a bias. Recently, information leakage was proposed as a source of the framing effect (McKenzie & Nelson, 2003;Sher & McKenzie, 2006). The basic idea is that the speaker's reference point is communicated (e.g., if people usually live or die) by his or her choice of frame.…”
Section: The Framing Paradoxmentioning
confidence: 99%
“…Some of the mechanisms proposed to explain attribute framing are concerned with the ways that differently framed statements are nonequivalent. The first possibility (Sher and McKenzie, 2006) is that two different logically equivalent frames may be informationally inequivalent because of information leakage: the communicator's choice of frame may contain information (e.g., the choice that the communicator favors) and this leaked information may be detected by the recipient of the communication (McKenzie and Nelson, 2003; Sher and McKenzie, 2006). The second possibility is that people interpret “60% replication rate” to mean “at least 60% have succeeded in replicating” and interpret “40% failure to replicate” to mean “at least 40% have failed to replicate” (Macdonald, 1986; Mandel, 2001).…”
Section: Introductionmentioning
confidence: 99%